oemof.solph—A model generator for linear and mixed-integer linear optimisation of energy systems - Krien, Uwe; Schönfeldt, Patrik; Launer, Jann; Hilpert, Simon; Kaldemeyer, Cord; Pleßmann, Guido (Software impacts, 2020)
Energy system modelling is of high importance to investigate different scenarios in their technical, economical and environmental feasibility. The interplay of different technologies and energy flows in respective models can be represented as directed graphs in a generic but comprehensible formalism. However, additional effort is needed to create specific models and to derive an optimal sizing or operation of components. To tackle this problem, oemof.solph facilitates the formulation of (mixed-integer) linear programs from a generic object-oriented structure. Its structure allows to create models on different levels of detail by means of predefined components and an optional formulation of additional expressions and constraints. With its open and documented code base, extensive collection of examples and an active community it is useful across many levels, from simple applications to advanced modelling. •Simplifies the generation of (mixed integer) linear problems of energy systems.•Highly customisable and extendable due to a generic and modular structure.•Open, transparent and well documented.•Used by research groups, individuals and companies.•Suitable for most energy fields and sector coupling.